TREND THRIFTING SEBAGAI ALTERNATIF OUTFIT KULIAH MAHASISWA FAKULTAS ILMU SOSIAL UIN SUMATERA UTARA - Fadly, Edward; Hrp, Elina Herawaty; Adnan, Hafizur Kahfi; Effendi, Erwan (UNIVERSITAS STEKOM, 2024)
Thrifting, or purchasing second-hand items, has become a popular cultural phenomenon in Indonesian society, particularly among budget-constrained students. This research employs a qualitative descriptive approach using in-depth interviews, observations, and literature studies to comprehend the impact and motivations of students adopting the thrifting lifestyle. The findings reveal that thrifting not only serves as an economic solution for students but also fosters unique and creative fashion styles. Additionally, this activity positively influences the environment by reducing waste and supporting charitable causes through the sale of second-hand items by non-profit organizations. Thrifting emerges as an alternative that allows students to stay up-to-date with fashion trends without compromising their budget balance. In conclusion, thrifting is more than a shopping activity; it is a lifestyle that reflects creativity, social responsibility, and the need to adapt to changing fashion trends.